Molecular confirmation of Gyroporus lacteus and typification of Boletus cyanescens - Vizzini, Alfredo; Angelini, Claudio; Ercole, Enrico (Phytotaxa, 2015)
Gyroporus lacteus is fully described based on recent collections from sandy areas in Italian littoral woods consisting of Pinus pinea and Quercus ilex. Léveillé’s plate 9 (1–2) (in Annls Sci. Nat., Bot., 1848) is selected as a lectotype and a recent sequenced collection as an epitype. Its independent position from Gyroporus cyanescens is supported by phylogenetic analyses of the nuclear ribosomal internal transcribed spacer (ITS) and the nuclear ribosomal large subunit (LSU) regions. In addition, Gyroporus cyanescens is typified by selecting Bulliard’s Plate 369 (in Herbier de la France 8, 1788) as a lectotype and a sequenced collection as an epitype.